Influence of the End Body Dynamics on Stabilization Processes in the Relative Motion of a Space Tethered System Stabilized by Rotation - Volosheniuk, O.L. (Наука та інновації, 2019)
Introduction. Space tethered systems (STS) stabilized by rotation is a quite interesting and promising direction in the field of cosmonautics. Such systems are intended for solving a wide range of scientific and research tasks, in particular, those that cannot be solved effectively with the help of the existing space technologies, for example, transport operations, creation of artificial gravity, removal of space debris objects, obtainment of experimental data of functioning tethered systems, etc. Problem Statement. The peculiarities of the STS dynamics models are determined by the specifics of the problems solved by such systems actual among which is the researches the effects of the end body dynamics on the system motion. Purpose. To build a mathematical model of the STS dynamics for considering the general regularities of the system motion and to analyze comprehensively the special features of the end body dynamics. Materials and Methods. The mathematical model of the STS dynamics has been built based on the methods and principles of theoretical mechanics and space flight dynamics. To study the STS dynamics, methods of the theory of oscillations, analytical and numerical integration of differential motion equations have been used. Results. The simplest model of the STS dynamics consisting of the material point and the end body connected by a tether is presented for the motion under consideration. The possibility of the appearance of internal resonances and their influence on the stabilization processes in the relative motion of the system has been considered. Conclusions. The proposed model can apply to analyzing the angular oscillation of the end body relative to the tether attachment point, taking into account the effects of the inertial characteristics of the end body, the tether stiffness and the angular velocity of the proper rotation of the system. Practical problems related to the STS dynamics may include the problems of the stability of the end body orientation, resonance modes in the system motion, as well as the problems in creating the prerequisites for the design of the specific STS. Вступ. Використання космічних тросових систем (КТС), стабілізованих обертанням, є досить новим і перспективним напрямком в галузі сучасної космонавтики. Такі системи призначені для вирішення широкого кола наукових та дослідницьких завдань, зокрема тих, які неможливо або неефективно вирішувати за допомогою наявних засобів космічної техніки, наприклад для транспортних операцій, створення штучної гравітації, відведення об’єктів космічного сміття, отримання експериментальних даних функціонування тросових систем тощо. Проблематика. Особливості моделей динаміки КТС зумовлені специфікою розв’язуваних такими системами завдань, актуальним серед яких є дослідження впливу динаміки кінцевого тіла на рух системи. Мета. Побудова математичної моделі динаміки КТС, яка дозволить розглянути загальні закономірності руху системи та виконати аналіз особливостей динаміки кінцевого тіла. Матеріали й методи. Побудова математичної моделі динаміки КТС базується на методах і принципах теоретичної механіки, методах динаміки космічного польоту. Для дослідження динаміки КТС використано методи теорії коливань, методи аналітичного та чисельного інтегрування диференційних рівнянь руху. Результати. Наведено найпростішу для досліджуваного руху модель динаміки КТС, що складається з матеріальної точки й кінцевого тіла, з’єднаних ниткою. Розглянуто можливість виникнення внутрішніх резонансів та їх вплив на процеси стабілізації у відносному русі системи. Висновки. Запропонована модель динаміки КТС дозволяє виконати аналіз кутових коливань кінцевого тіла відносно точки кріплення до нитки з врахуванням впливу інерційних характеристик кінцевого тіла, жорсткості нитки й кутової швидкості власного обертання системи. До практичних питань, пов’язаних з цією задачею динаміки КТС, можна віднести питання стійкості орієнтації кінцевого тіла, питання про резонансні режими в русі системи, а також питання про створення необхідних передумов для проектування конкретних КТС. Введение. Использование космических тросовых систем (КТС), стабилизированных вращением, является достаточно новым и перспективным направлением в области современной космонавтики. Такие системы предназначены для решения широкого круга научных и исследовательских задач, в частности, тех, которые невозможно или неэффективно решать с помощью имеющихся средств космической техники, например для транспортных операций, создания искусственной гравитации, увода объектов космического мусора, получения экспериментальных данных функционирования тросовых систем и т. д. Проблематика. Особенности моделей динамики КТС обусловлены спецификой решаемых такими системами задач, актуальными среди которых являются исследования влияния динамики концевого тела на движение системы. Цель. Построение математической модели динамики КТС, которая позволит рассмотреть общие закономерности движения системы и выполнить анализ особенностей динамики концевого тела. Материалы и методы. Построение математической модели динамики КТС базируется на методах и принципах теоретической механики, методах динамики космического полета. Для исследования динамики КТС использованы методы теории колебаний, методы аналитического и численного интегрирования дифференциальных уравнений движения. Результаты. Представлена простейшая для исследуемого движения модель динамики КТС, состоящая из материальной точки и концевого тела, соединенных нитью. Рассмотрена возможность возникновения внутренних резонансов и их влияние на процессы стабилизации в относительном движении системы. Выводы. Предложенная модель динамики КТС позволяет выполнить анализ угловых колебаний концевого тела относительно точки крепления к нити с учетом влияния инерциальных характеристик концевого тела, жесткости нити и угловой скорости собственного вращения системы. К практическим вопросам, связанным с данной задачей динамики КТС, можно отнести вопросы устойчивости ориентации концевого тела, вопросы о резонансных режимах в движении системы, а также вопросы о создании необходимых предпосылок для проектирования конкретных КТС.